The Efficiency of KSPPS BMT UGT Nusantara Branches in East Java using Data Envelopment Analysis (DEA) Period 2018-2022 - Jaudat Iqbal Harris; Sirajul Arifin; Muhammad Yazid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Performance assessment of Islamic financial institutions such as KSPPS BMT UGT Nusantara is crucial to ensure optimal resource utilisation and improved customer service. This study evaluates the efficiency of several branches of KSPPS BMT UGT Nusantara in East Java from 2018 to 2022 using the Data Envelopment Analysis (DEA) approach. Input variables include the number of employees, total assets, and operational costs, while output variables encompass the number of customers, total financing, and total income. The results show that during the 2018-2022 period, many branches of BMT UGT Nusantara had not yet reached optimal scale, although some had achieved efficiency levels in both production and intermediation approaches. In the production approach, 50% of branches achieved technical efficiency, pure technical efficiency, and scale efficiency, while in the intermediation approach, 55% of branches achieved the same efficiency levels. To address inefficiencies, recommended strategies include: adjusting the number of employees according to actual needs; reducing excessive operational costs by identifying and eliminating unnecessary expenses; and managing assets more effectively by reinvesting in revenue-generating activities.